Evaluating the Association of Regional and City-Level Environmental Greenness and Land Over Patterns With PM2.5 Pollution: Evidence From the Shanxi Province, China - Guo, Guangxing; Liu, Liwen; Duan, Yonghong (Frontiers in Environmental Science, 2022)
Ambient PM2.5 (fine particulate matter with aerodynamic diameters ≤2.5 μm) is a major threat to human health. Environmental fates and human exposure to PM2.5 can be affected by various factors, and environmental greenness have been documented to be significantly associated with the exposure disparities; however, the relationship between the greenness and ambient PM2.5 on the region and city levels, and variations across different land cover types remain unclear. In this study, PM2.5 changes from 2001 to 2020 varying over different land cover types and cities were analyzed, and discussed for the relationships with environmental greenness, by taking Shanxi province as an example. The results showed in the past 2 decades, the mean annual NDVI (normalized difference vegetation index) of the study area showed a significant increasing trend (p < 0.01), and the PM2.5 concentration decreased as environmental greenness get better. The same trends were observed across different land cover types and cities. The negative correlation was stronger in the construction land with more frequent human activities, especially in the built-up areas with low vegetation coverage; but limited in the high green space coverage areas. These results provide quantitative decision-making references for the rational development, utilization and management of land resources, but also achieving regional coordinated controls of PM2.5 pollution by optimizing land use.